Rancang Bangun Sistem Keamanan Pintu Rumah Menggunakan Arduino Berbasis Android - Eko Setyo Budi Putra Aji; Rika Rosnelly (LPPM Universitas Potensi Utama, 2023)
Many people still find it difficult to secure their doors with the current technological orientation. Many people look for safety devices for their doors on various websites, but they are still constrained by the price and how to install the equipment purchased on their door. The existence of tools and applications for designing a home door security system is made with the aim of helping people to secure their door in an easier and more efficient way. The design of the home door security system with the available Android-based Arduino makes it easier for people to secure their home doors, of course, with guides and understanding of the tools described by the author. Tools made using Arduino and applications are made using the Java programming language. The system development, method for making this application uses the MIT App Inventor.